2011
DOI: 10.1016/j.peptides.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Altered dipsogenic responses and expression of angiotensin receptors in the offspring exposed to prenatal high sucrose

Abstract: The present study determined water and salt intake as well as expression of AT1 and AT2 receptors in the brain and kidney in the adult offspring rats prenatally exposed to high sucrose. Following the exposure during pregnancy, water intake and salt intake at baseline levels were not changed in the adult offspring. However, after 24 hour water deprivation, consumption of water and salt was significantly increased compared to that of the control. Plasma sodium and osmolality levels remained the same between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Pregnant Sprague-Dawley rats from the Animal Center of Soochow University were randomly divided into two groups: (1) the control group fed with standard food and tap water and (2) the HS group provided with the same food with 20% sucrose solution since gestational day 1 as reported. 15 After delivery, all maternal rats were provided tap water and standard rat food, and the baby rats were given breast feeding. After weaning, the offspring rats from both groups were given tap water and standard rat food for 5 months.…”
Section: Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant Sprague-Dawley rats from the Animal Center of Soochow University were randomly divided into two groups: (1) the control group fed with standard food and tap water and (2) the HS group provided with the same food with 20% sucrose solution since gestational day 1 as reported. 15 After delivery, all maternal rats were provided tap water and standard rat food, and the baby rats were given breast feeding. After weaning, the offspring rats from both groups were given tap water and standard rat food for 5 months.…”
Section: Methods Animalsmentioning
confidence: 99%
“…8 Growing evidence suggested that prenatal insults, including malnutrition, high salt diet, hypoxia and dehydration during pregnancy, could adversely affect cardiovascular conditions in offspring. [9][10][11][12][13][14] Our previous study has shown that maternal intake of high sucrose (HS) could increase blood glucose in the maternal rats, and affect fetal and offspring's development, 15 evidenced as increased fetal body weight. However, little is known about how maternal HS intake during pregnancy affects vascular functions in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, high sugar exposure during fetal development can also program fluid intake in adult life. Studies have shown that fetal exposure to a high sucrose solution at the end of pregnancy induced increased expression of the AT 1 and AT 2 receptor proteins in the forebrain in adult animals, although there were no significant differences in water or hypertonic saline intake compared with controls in need-free conditions (Wu et al, 2011).…”
Section: Other Developmental Influences On the Programming Of Fluid Intakementioning
confidence: 96%
“…Although several terms for mice were included in the database search, only rat studies were identified. Eleven of the included papers used Sprague-Dawley rats, 31,[38][39][40][41][42][43][44][45][46][47] three used Wistar rats 30,48,49 and one did not report strain type. 29 Sucrose was administered at either 10% w/v [29][30][31]48,49 or 20% w/v 29,[38][39][40][41][42][43][44][45][46][47] and maternal exposure ranged from 16 to 126 days, including periods during pre-conception, gestation and lactation.…”
Section: Study Characteristics and Designmentioning
confidence: 99%
“…Eleven of the included papers used Sprague-Dawley rats, 31,[38][39][40][41][42][43][44][45][46][47] three used Wistar rats 30,48,49 and one did not report strain type. 29 Sucrose was administered at either 10% w/v [29][30][31]48,49 or 20% w/v 29,[38][39][40][41][42][43][44][45][46][47] and maternal exposure ranged from 16 to 126 days, including periods during pre-conception, gestation and lactation. The majority 29,30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] employed a compulsory drinking paradigm with sucrose solution being the only source of drinkin...…”
Section: Study Characteristics and Designmentioning
confidence: 99%